Companion planting with white yarrow or with feverfew for squash bug, Anasa tristis (Hemiptera: Coreidae), management on summer squash. Issue 6 (20th October 2016) - Kahn, Brian A; Rebek, Eric J; Brandenberger, Lynn P; Reed, Keith; Payton, Mark E
Abstract: BACKGROUND: The squash bug, Anasa tristis (De Geer), is a major insect pest of cucurbits. Control of squash bugs with insecticidal chemicals is difficult to achieve. We investigated the potential of companion planting with white yarrow ( Achillea millefolium L.) or feverfew [ Tanacetum parthenium (L.) Sch. Bip.] for squash bug management in field plantings of summer squash ( Cucurbita pepo L.). RESULTS: Companion planting with white yarrow had few effects. Companion planting with feverfew tended to reduce squash bug populations, but results often were not statistically significant ( P ≥ 0.05). Early‐season ventilated row covers (without herbs) neither reduced squash bug populations nor increased squash yields. Herbs reduced marketable squash yields compared with the control only once out of seven experiments. CONCLUSION: The tested companion planting strategies inconsistently affected squash bug populations on summer squash. Therefore, these strategies are not recommended to commercial producers. © 2016 Society of Chemical Industry